2012
DOI: 10.1111/j.1540-8159.2012.03514.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Recurrence Rate in Treating Atrioventricular Nodal Reentrant Tachycardia with Triple Freeze‐Thaw Cycles

Abstract: Triple FTC cryoablation lesions resulted in a low recurrence rate comparable to RF ablation in treating AVNRT without increased complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…atrial flutter), and further studies will determine their efficacy in children. Finally, as most studies on cryoablation of AVNRT in children report acute success rates ranging between 90 and 100%, RFCA was at least equally successful in our study cohort .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…atrial flutter), and further studies will determine their efficacy in children. Finally, as most studies on cryoablation of AVNRT in children report acute success rates ranging between 90 and 100%, RFCA was at least equally successful in our study cohort .…”
Section: Discussionsupporting
confidence: 64%
“…Probably, the advantage of creating a lesion, which is, depending on the freezing time, partially reversible, also accounts for a higher risk of only subtotal ablation of the arrhythmogenic substrate, which finally results in higher recurrence rates. Supporting these theories, two recently published studies found that a change of policy to a triple freeze-thaw technique, or the use of a larger (8 mm) tip catheter, resulted in remarkably low recurrence rates of 2% (9,10).…”
Section: Discussionmentioning
confidence: 94%
“…no jump or echo beats [17]. Data from the pediatric literature suggests that acute success can be seen in 96.2% of patients, with a triple freeze-thaw cycle [16]. In this group, the recurrence rate was 2.0% (1 patient).…”
Section: Discussionmentioning
confidence: 82%
“…Despite this, the long term recurrence rate appears to be acceptable at 8%. Other recent studies suggest that improved outcomes with cryoablation of AVNRT, perhaps comparable to radiofrequency ablation, may be achieved with 8 mm tip catheters [13], [14], linear ablation in the inferior portion of Koch's triangle [15], freeze-thaw-freeze cycles [16], and eliminating slow pathway conduction completely i.e. no jump or echo beats [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation